2013
DOI: 10.1108/00483481311320426
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high performance work systems on voluntary turnover of new hires in US state governments

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 116 publications
1
31
0
3
Order By: Relevance
“…According to Cropley (2015), Häkkinen et al (2017) and Kereluik et al (2017), creativity and innovation are vital for teachers to help students learn well. Literature has suggested that intrinsic motivation, HPWS, knowledge sharing, and authentic leaders are the key factors among others which promote creativity in an organization (Andreeva & Sergeeva, 2016;Fareed et al, 2016;Lin, 2007;Malik et al, 2015Malik et al, , 2016Paracha et al, 2014;Selden et al, 2013;Zhang et al, 2014;Zhang, 2010). Previous researchers explored a direct relationship between HPWS and performance or HPWS was taken as mediating variable along with other variables (Fareed et al, 2016;Heffernan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Cropley (2015), Häkkinen et al (2017) and Kereluik et al (2017), creativity and innovation are vital for teachers to help students learn well. Literature has suggested that intrinsic motivation, HPWS, knowledge sharing, and authentic leaders are the key factors among others which promote creativity in an organization (Andreeva & Sergeeva, 2016;Fareed et al, 2016;Lin, 2007;Malik et al, 2015Malik et al, , 2016Paracha et al, 2014;Selden et al, 2013;Zhang et al, 2014;Zhang, 2010). Previous researchers explored a direct relationship between HPWS and performance or HPWS was taken as mediating variable along with other variables (Fareed et al, 2016;Heffernan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade or so, a great deal of research has been conducted on the individual and organisational outcomes of high-performance work systems (HPWSs), such as job performance (Shih et al, 2013), voluntary turnover (Selden et al, 2013), discretionary behaviour (Elorza et al, 2016) and firm performance (Messersmith and Guthrie, 2010) (see also Kaufman, 2015 for an overview and critique). However, comparatively few studies have investigated the influence of HPWS on employee creativity (Chiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is an argument whether using one approach is the best choice or taking the benefits of each approach will be better for organizations as each approach has particular practices making it distinguished, the universalistic approach has certain practices which make any organization adopt it quickly and having its benefits, The contingency is better to have practices suitable to different organizational contexts, yielding more performance can be achieved by applying the configurationally perspective. There are other studies explaining HRMS: Arther (1994) shows that HRMS depends on controlling human resources management; McClean and Collins (2011) stated that HRMS is conducting high-commitment HR systems; Selden et al (2013) explained that HRMS works on achieving high-performance work systems. Moreover, Ichniowski et al, (1997) highlighted that HRMS priorities are a must for having innovative HRM systems.…”
Section: Literature Reviewmentioning
confidence: 99%